LITERASI REFERENSI ILMIAH DI PERGURUAN TINGGI : KONSEP DAN MANFAATNYA DALAM MEMBANTU MAHASISWA DALAM MENULIS DAN MEMPUBLIKASIKAN KARYA ILMIAH - Andi Saputra (VISI PUSTAKA: Buletin Jaringan Informasi Antar Perpustakaan, 2020)
The digitalization of scientific reference sources has moved library collections into the virtual realm, in the form of online databases. Thus bringing up new studies in the field of information literacy. This study aims to develop the concept of scientific reference literacy based on user perceptions in college, and measure the needs and benefits for students. The concept was given in the form of training for Andalas University graduate students. To see the effect before and after the training participants were asked to fill out a questionnaire, related to their understanding of the sources of scientific references, and their perceptions of the training material, as well as the benefits they felt. The results of the study showed that before the training they still had difficulty in finding and obtaining reference sources for writing the final project. The concept of online reference literacy given to them turned out to be very useful in increasing their understanding of scientific reference sources in supporting research or writing and publication of scientific papers. In conclusion, although students currently belong to the native digital generation, who are already familiar and adept at using information technology. However, they still need guidance in utilizing scientific reference sources. They must be guided from the first year students. The college must provide a specific time allocation for this training, which is followed by periodic writing of scientific papers by the librarian to ensure that the material presented at the training can be well understood by the participants.